การพัฒนารูปแบบการมีส่วนร่วมในการจัดสวัสดิการชุมชนชาวประมงชายฝั่งทะเลอันดามัน - Jirachaya Jeawkok จิรัชยา เจียวก๊ก; Wanchai Dhammasaccakarn วันชัย ธรรมสัจการ; Kasetchai Laeheem เกษตรชัย และหีม; Utit Sangkarat อุทิต สังขรัตน์ (Journal of Social Development and Management Strategy, 2017)
การศึกษาครั้งนี้มีวัตถุประสงค์เพื่อศึกษาการมีส่วนร่วมในการพัฒนารูปแบบการจัดสวัสดิการชุมชนชาวประมงชายฝั่งทะเลอันดามันในภาคใต้ของประเทศไทย โดยใช้วิธีวิจัยเชิงคุณภาพด้วยการสังเกตและการสัมภาษณ์แบบเจาะลึกจากผู้ที่ได้รับ และไม่ได้รับสวัสดิการ ผู้จัดสวัสดิการในชุมชน รวมจำนวน 11 คน วิเคราะห์ข้อมูลโดยการนำข้อมูลมาจัดหมวดหมู่ตามประเด็น ถอดรหัส ตีความ และเรียบเรียงข้อมูล ผลการวิจัยพบว่า ชุมชนมีการพัฒนารูปแบบการจัดสวัสดิการชุมชนโดยอาศัยการมีส่วนร่วมของคนในชุมชน ตั้งแต่ริเริ่ม วางแผน ดำเนินการ รับผลประโยชน์ และประเมินผล ซึ่งมีทำงานภายใต้หลักการของชุมชน “ร่วมคิด ร่วมทำ ร่วมได้ ร่วมรับผิดชอบ” ขณะที่ผู้นำเองจะต้องมีบทบาทสูงในการประสานความคิดและกระตุ้นการทำงานของคนในชุมชน ขับเคลื่อนผ่านกลุ่มอาชีพ และวิสาหกิจชุมชนโดยให้ความสำคัญกับการเรียนรู้เพื่อพัฒนาระบบการพึ่งตนเอง รวมถึงการมีหน่วยงานภาครัฐและเอกชนเป็นผู้ให้การสนับสนุน ฉะนั้นหน่วยงานภาครัฐควรดำเนินพัฒนารูปแบบโดยอาศัยการมีส่วนร่วมของคนในชุมชน จะทำให้คนในชุมชนได้แสดงศักยภาพและพึ่งตนเองได้อย่างยั่งยืน This study aimed to study the participation in the development of the fishing community welfare model of Andaman coast in the southern Thailand. This study was the qualitative research with the intensive interview and the observation as the research instruments from 11 local community welfare receivers and non-receivers. The result was analyzed from classifying, encoding, interpreting and compiling the data effectively. The finding result was that the community developed a community welfare model which based on the collaborative work of the people in the community from the stage of initiating, planning, executing, receiving benefits, and evaluating under the principle of "co-participate, participate and share responsibility" Leaders must play a strong role in coordinating ideas and motivating people work in the community, drive through the professional and community enterprise, which a focus on learning to develop the self-reliant systems including the government and private agencies as the supporters. Therefore, government agencies should develop the participation of people model which showed their potential and self-sustainability.